Reconstructing a Late Archaic-Period Dionysian Ship Cart - Wachsmann, Shelley; Sanders, Donald H. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The Greek deity Dionysos had a particular affinity for war galleys, a relationship perhaps explained by the Homeric Hymn to Dionysos in which Tyrsenian pirates kidnap him on their galley. Soon grape vines entangle the rigging and some of the pirates attempt to escape their fate by jumping into the sea: Dionysos transforms them into dolphins. This hymn served as an occasional motif in pagan art and may explain the miniaturized replicas of seagoing oared ships that played an integral role in the ancient Dionysian cult. These flimsy Dionysian ship carts moved overland in parades, either on wheels or upon the shoulders of celebrants. While the earliest examples may date to the Late Bronze Age, they are best known from a series of three late Archaic-period representations on black-figure skyphoi, now in museums in Athens, Bologna and London. No two Archaic-period Dionysian ship-cart representations are identical in all details. While perhaps due to painters’ whims, this diversity in appearance may reflect changes to the ship carts at each annual appearance, analogous to modern-day parade floats. Due to the two-dimensional nature of these ship-cart images, it is impossible today to determine whether the Dionysian ship carts reflected in them consisted of actual vessels—purpose-built and placed on wagons during the procession, employed solely for the Dionysian celebrations—or floats in the form of miniaturized galleys. This paper supplies context and explains the process of creating a three-dimensional digital reconstruction of a generic Late Archaic-period Dionysian ship cart employing contemporaneous imagery and artifacts.the ship carts at each annual appearance, analogous to modern-day parade floats. Due to the two-dimensional nature of these ship-cart images, it is impossible today to determine whether the Dionysian ship carts reflected in them consisted of actual vessels—purpose-built and placed on wagons during the procession, employed solely for the Dionysian celebrations—or floats in the form of miniaturized galleys. This paper supplies context and explains the process of creating a three-dimensional digital reconstruction of a generic Late Archaic-period Dionysian ship cart employing contemporaneous imagery and artifacts.
Keywords: Bacchus; cult; digital archaeology; Dionysos; nautical archaeology; ship cart; skyphoi; virtual heritage; virtual reality; 3D modeling